MENINGKATKAN KEMAMPUAN BERBAHASA MELALUI METODE BERMAIN PERAN DI PAUD MUTIARA BUNDA JL.KH HASYIM 4A KECAMATAN PADEMAWU KABUPATEN PAMEKASAN TAHUN AJARAN 2021-2022 - Moh Rosidi; Wahono Wahono; Naili Sa’ida (Universitas Muhammadiyah Surabaya, 2022)
The purpose of this study was to determine Language Ability through Role Playing Method at Mutiara Bunda Early Childhood Education Jl.Kh Hasyim 4a Pademawu District, Pamekasan Regency, 2021-2022 Academic Year. Language is the ability to communicate with other people. In this sense, it includes all ways to communicate, where thoughts and feelings are expressed in the form of symbols or symbols to express an understanding, such as by using spoken, written, number signs, paintings, and facial expressions. The research method used in this research is qualitative. With research procedures that include preliminary studies, planning, implementing actions, observing and reflecting. The result of this research is that the children's language ability level Â at Â JL.KH Â Wachid Â Hasyim Â 4A Â Kec. Â Pademawu Â Kab. Â Pamekasan Â for Â the Â academic Â year 2021/2022 as a whole has not experienced a significant improvement as the standard of research success that was previously set, it is proven that the implementation of the actions in Cycle I of children who got good grades from 6 to 40%, at adequate scores to 9 children was 60% and a low score was 0. 0% But In Cycle I This Increase Is Not In Accordance With What Was Expected.Â Keywords: reflection; qualitative; value; significant